KEPEMIMPINAN DAN TEAMWORK DALAM MEMBANGUN BUDAYA MUTU PENDIDIKAN PERSPEKTIF TOTAL QUALITY MANAGEMENT - Hafid Abdul Gani; Syaikhul Kubro; Diky Herisnawan (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of leadership and teamwork in building a culture of educational quality from the perspective of Total Quality Management (TQM). TQM is a management approach that emphasizes continuous quality improvement through the involvement of all components within educational organizations. In its implementation, leadership and teamwork are essential elements in creating an effective quality culture oriented toward improving the quality of educational services. This study employs a qualitative approach using the library research method. Data were collected from various books, scientific journals, and relevant literature related to TQM, educational leadership, teamwork, and educational quality culture. Data analysis was conducted through content analysis involving data reduction, categorization, and descriptive-analytical conclusion drawing. The findings reveal that leadership plays a strategic role as the primary driving force in implementing a quality culture through the establishment of a quality vision, effective communication, motivation, and strengthening organizational commitment. Meanwhile, teamwork functions as a means of collaboration and coordination among organizational members in supporting continuous improvement and enhancing work effectiveness. The synergy between leadership and teamwork is able to create a collaborative culture, improve professionalism, strengthen educational innovation, and continuously enhance the quality of educational services.